Empirical Study Of The Influence Of Cash Flow Components And Gross Profit On Stock Prices Of Manufacturing Companies In Indonesia Stock Exchange - Jadongan Sijabat (International Journal Reglement & Society (IJRS), 2022)
Financial statements are an important tool for investors and creditors to know the company's development periodically because financial statements are a very important source of information and are needed by users of financial statements. Investors and creditors use cash flow information as a measure of company performance, because information about cash flows is used as a basis for assessing the company's ability to generate cash and cash equivalents and assessing the company's need to use these cash flows. In addition to cash flow, the company's performance parameter that is the main concern is profit. This study focuses on gross profit because gross profit can better describe the relationship between earnings and stock prices. This study aims to examine the effect of cash flow components (operating activities, investment activities, funding activities) on stock prices. In addition, this study also aims to examine the effect of gross profit on stock prices. This study uses a multiple regression research method with a sample of 45 manufacturing companies listed on the Indonesia Stock Exchange from 2018 - 2020. The analytical tool used is the SPSS version 26 program. The results obtained in this study are that the variables of operating activities, investment activities, funding activities, and gross profit simultaneously have a significant effect on stock prices. Partial testing shows that only funding activities variables and gross profit have a significant effect on stock prices.